Big Data Analytics: A Catalyst for Digital Transformation in e-Government - Vasilopoulou, Christina; Theodorakopoulos, Leonidas; Giotopoulos, Konstantinos (Technium Social Sciences Journal, 2023)
This paper explores the role of Big Data Analytics (BDA) in e-Government and how it can act as a catalyst for digital transformation. The paper begins by defining e-Government and digital transformation, and then moves on to explain the concept of BDA. The benefits of using BDA in e-Government are then discussed, such as data-driven decision-making and improved citizen engagement. However, there are also challenges to consider, including privacy and security concerns and a lack of skilled professionals. The essay provides case studies of governments that have successfully used BDA to transform their operations and service delivery. In conclusion, BDA has the potential to transform e-Government, but governments must invest in this technology and address the challenges associated with its implementation.